Association of The Invasive Plant Acrostichum aureum with Flora of Degraded Mangrove Forests - Rizki Wahyudi; Syaiful Eddy; Dian Mutiara (Jurnal Biologi Tropis, 2026)
The mangrove ecosystem in the Air Telang Protected Forest (ATPF), Banyuasin Regency, has experienced ecological pressure due to land conversion, which has facilitated the proliferation of invasive species in degraded areas. This study aimed to analyze plant association patterns in mangrove areas affected by the dominance of Acrostichum aureum. The research employed a descriptive method with a purposive sampling approach across four observation stations. Interspecific associations were analyzed using the Jaccard Index based on species presence data collected during the study. The results revealed 36 plant species associated with A. aureum. Similarity values among stations ranged from 0.1 to 0.53, with the highest similarity observed between Stations 2 and 3 and the lowest between Stations 3 and 4. Association values between A. aureum and other species ranged from 0.25 to 1.00, with very high associations recorded for Nypa fruticans and Schoenoplectus subulatus, and high associations for Acanthus ilicifolius and Derris trifoliata. The dominant association types identified were positive and neutral associations, with Derris trifoliata, Nypa fruticans, Acanthus ilicifolius, and Schoenoplectus subulatus exhibiting positive associations with A. aureum. Ecologically, the presence of A. aureum plays a role in shaping species distribution patterns through interactions influenced by environmental heterogeneity and habitat conditions.